Revolutionizing biotech and pharmaceutical education with adaptive learning - Wang, Tao; Xu, Na; Liu, Fei (Frontiers in Education, 2025)
Adaptive learning systems (ALSs), powered by artificial intelligence (AI), represent a transformative approach to biotechnological and pharmaceutical education that addresses the critical limitations of traditional standardized pedagogy. This review highlights empirical evidence demonstrating how ALS dynamically personalizes learning through knowledge state modeling (KSM) and the synergistic integration of knowledge level (KL) and knowledge structure (KS) dimensions. This framework enables mastery-based progression in sequential domains (e.g., genetic engineering and pharmacodynamics), ensuring foundational competency before advancement. In addition, key applications of adaptive learning (AL) in the field of biological and pharmaceutical education are also detailed, including scaffolding complex foundational sciences (e.g., real-time misconception detection in Clustered Regularly Interspaced Short Palindromic Repeats—CRISPR-associated protein 9 [CRISPR-Cas9]), enhancing technical skills via AI-driven virtual labs simulating industry workflows (e.g., High-Performance Liquid Chromatography [HPLC] and bioreactors), and navigating regulatory compliance through contextual simulations. The documented benefits include significant cost reduction, accelerated skill acquisition, and strengthened industry alignment. Nevertheless, challenges persist in terms of technical fragmentation, algorithmic bias, and equitable resource access. Finally, it is suggested that future research priorities should involve developing integrated architectures with blockchain-secured micro-credentials, human-AI synergy frameworks for ethical oversight, and equity-driven deployment via federated edge learning. The strategic implementation of ALS promises to cultivate a globally competitive, interdisciplinary workforce for next-generation biopharmaceutical innovation while establishing rigorous, regulatory-grade training.